Analysis of Kalam Sects' Content in Akidah Akhlak Learning at Madrasah Aliyah - Ifkar; Muhammad Taslim; Adona, Putri (Al Bahri: Journal of Islamic Education, 2025)
The kalam science is a discipline of Islamic theology that focuses on explaining and defending the teachings of faith through a rational approach. The purpose of this study is to analyse the material of the kalam science genre in the learning of akidah akhlak in madrasah Aliyah. The research method used is a qualitative method with a content analysis approach, where the source of the book is the Akidah Akhlak textbook published by the Ministry of Religion of the Republic of Indonesia. After conducting an in-depth analysis, the author can find the structure of the material of the school of kalam science in learning moral creed in Madrasah Aliyah consisting of related to its history, various schools of thought emerged, including Mu'tazilah which emphasised rationality and divine justice, Asy'ariyah which combined tradition with rationality, Maturidiyah which emphasised the role of reason and freedom of human will, Jabariyah which believed in determinism, and Qadariyah which taught full human freedom. The history of the comparative teachings of kalam includes debates between these schools as well as interactions with other thoughts and cultures, discussing concepts such as reason and Revelation, Imam and Kufura of human actions, absolute will and God's justice. In the future, the author hopes that this research will have a positive impact, especially in madrasah as formal educational institutions with the characteristic of instilling Islamic values to their students.